CYTOKINE GENE EXPRESSION ASSOCIATED WITH TUMOR AND PREMETASTATIC NICHES IN BREAST CANCER STROMA - L. A. Tashireva; T. S. Geraschenko; M. V. Zavyalova; O. E. Saveleva; E. V. Kaygorodova; N. A. Tarabanovskaya; E. M. Slonimskaya; E. V. Denisov; V. M. Perelmuter (Сибирский онкологический журнал)
The tumor niche in the microenvironment of the primary tumor is believed to reflect events occurring in the premetastatic niche. In our study, based on the assessment of the expression of cytokine genes associated with inflammation and invasive and metastatic phenotype of tumor cells in the tumor microenvironment, their contribution to the creation of favorable conditions for the development of tumor and metastases was described. Material and methods. The main clinical and pathological parameters in 12 patients with invasive breast carcinoma of non-specific type (IC NST) were studied. The expression of 13 genes encoding key cytokines and chemokines in the stroma of IC NST was assessed using the PALM laser microdissection system and real-time polymerase chain reaction. Results. A direct correlation between the size of the primary tumor and the expression levels of IL1b and CXCL8 genes was found. Furthermore, it was shown that the proliferative activity of tumor cells was inversely correlated with the expression CCL2 gene that attracted monocytes. The expression of IL6 and IL8 genes involves the differentiation of monocytes into M2 macrophages, which can stimulate tumor cell invasiveness. However, microenvironment cells were found not to express MST1, FGF7, EGF genes, protein products of which provide invasive and metastatic progression of tumor cells. In our study, no significant differences in gene expression levels between patients with and without lymph node metastases were found. Nevertheless, the use of the multivariate data analysis allowed us to reveal a close relationship between the studied parameters related to a high risk of lymph node metastasis. Conclusion. A wide range of cytokines involved in the development of inflammation, recruitment of monocytes, as well as secretion of factors promoting both tumor growth and lymphatic metastasis was identified. Similar events in premetastatic niche might contribute to the development macrometastasis.